Gastric Electrical Stimulators Causing Erosion Through the Colonic Wall. Issue 2 (2nd February 2020) - Condon, Sally; Patel, Aniruddh; Shah, Nihar; Stocker, Abigail; Hughes, Michael; Farmer, Russell; Abell, Thomas
ABSTRACT: Gastroparesis is a chronic motor disorder of the stomach characterized by the demonstration of delayed gastric emptying without obstruction and a grouping of symptoms including nausea, vomiting, early satiety, postprandial fullness, bloating and abdominal pain. When conservative medical management is not effective, gastric electrical stimulation is an effective alternative. Gastric electrical stimulation, in general, has had a low complication rate as of yet, with the most common being infection of the implanted device. We present a complication in which the gastric electrical stimulator electrodes eroded through the colonic wall.